Analysis Of Career Interests Of Business Education Students Of Stambuk 23 In Entrepreneurship And Teacher Education And Its Implications For The Course - Dilla Syadzwina; Fahmi Ashari S Sihaloho (CV Pena Jaya Pers, 2025)
This study aims to analyze the comparative interest of Business Education students of Stambuk 23 towards the world of entrepreneurial business and teacher education and its implications for the courses of the Business Education Study Program at Medan State University. In the era of globalization and rapid technological development, higher education is faced with various new challenges and opportunities. 21st century skills have received significant attention due to the demands of the world of work and the needs of society that are growing rapidly. This study used qualitative methods in the form of interviews and questionnaires to collect data from 38 students. The results showed that the majority of students were more interested in becoming entrepreneurs (76.32%) than academics (23.68%). Factors that influence this interest include educational background, experience, and personal perceptions of career prospects. Students who are interested in the academic world tend to be influenced by the family environment that has a career in the academic field and prefer to become lecturers rather than teachers in business-based vocational schools. This study highlights the mismatch between student interests and the graduate profile expected by the study program. Therefore, adjustments are needed in the curriculum and courses to meet the needs and aspirations of students and remain in line with the desired graduate profile. This study provides practical recommendations for the development of more responsive and adaptive courses, so that graduates of the Business Education study program can be better prepared to face challenges in the world of work and make meaningful contributions to society.